A Simple Protocol for Isolating Small RNA from Cassava (M anihot esculenta Crantz) - Deepthi, D C; Makeshkumar, T (JOURNAL OF ROOT CROPS, 2016)
Small RNAs of 20-30 nucleotide are involved in re gulatory processes at DNA or RNA levels in many eukaryotic plant systems. Good and efficient protocols to isolate small RNAs are needed for characterization. A simple method for isolating small RNAs from virus infected plant species has been developed. The method involves precipitation of low molecular weight RNA using NaCl, PEG 8000 and LiCl. The purity of isolated small RNA was confirmed by A260/280 and A260/230 ratio. The described protocol also resulted in isolation of sufficiently higher yield of small RNA from virus infected leaf samples of cassava. The current protocol can be completed in a day and is cost effective. With regard to cost, the per sample cost associated with commercially available kits were approximately 32 times and for Trizol it is 5 times higher than that of current protocol.